Effect of rare earth elements on plasma electrolytic carbonitriding of Ti–6Al–4V alloy. Issue 18 (12th December 2019) - Chen, Feifei; Yu, Shouxin; Lu, Wenzhuang; Pang, Jing; Tian, Wanshan; Sun, Yuli; Zuo, Dunwen
ABSTRACT: The paper aims to research the effect of rare earth elements on the carbonitriding layer of titanium alloy by establishing a theoretical model between rare earth concentration and atomic diffusion efficiency. It shows that adding rare earth can not only refine the discharge holes, but also reduce surface cracks, which significantly improve the surface quality of the strengthening layer. It is also found that an appropriate amount of rare earth can greatly increase the growth rate of the carbonitriding layer and carbon content near the surface. Furthermore, compared with the conventional plasma electrolytic carbonitriding treatment, adding 2 g L −1 cerium oxide can effectively reduce the activation energy of carbon, so as to improve its diffusion ability.